Spatiotemporal Evolution Characteristics of Fluid Flow through Large-Scale 3D Rock Mass Containing Filling Joints: An Experimental and Numerical Study. (4th January 2021) - Yin, Qian; Jing, Hongwen; Zhu, Tantan; Wu, Lizhou; Su, Haijian; Yu, Liyuan
Abstract : This study analyzes the spatiotemporal evolution characteristics of seepage through a large-scale rock mass containing a filling joint. Firstly, a conceptual model was established to characterize the geomechanical occurrence of a typical water-resistant slab adjacent to a water-bearing structure. Then, a special apparatus was developed to conduct a hydromechanical test of a 3D large-scale rock mass. For a certain boundary stress and inlet water pressure, the pore water pressure in the joint first experiences a dramatic increase before approaching a constant value, and the steady pore water pressure presents a linear decrease along the joint length. A water inrush phenomenon happens as a result of connected flowing channels induced by migration of fillings. Using the finite element of COMSOL multiphysics, the influences of filling joint permeability, matrix permeability, and joint thickness as well as the inlet water pressure on seepage evolution in the jointed rock mass were, respectively, investigated. The pore water pressure increases with all these factors, and the stable pressure values increase with the inlet water pressure but decrease along the joint length. The flow velocity undergoes an increase with both the joint permeability and inlet water pressure but presents constant values independent on the matrix permeability or joint thickness. The water pressure contour planes distributed along the flowing path generally transfer from a "long funnel" shape to a "short funnel" shape before reaching a series of parallel pressure planes perpendicular to the joint direction. By using the genetic algorithm, the coupling influences of these factors on the pore water pressure and flow velocity were investigated, and the decision parameters were optimized. The calculated values show a good agreement with the numerical results, indicating a good prediction of the seepage evolution through the filling joint.